Art and politics : a small history of art for social change since 1945 - Mesch, Claudia (London : I.B. Tauris, 2013)
Contemporary art is increasingly concerned with swaying the opinions of its viewer. To do so, the art employs various strategies to convey a political message. This book provides readers with the tools to decode and appreciate political art, a crucial and understudied direction in post-war art.
State-sponsored art during the Cold War -- Post-colonial identity and the Civil-Rights movement -- The anti-war and peace movements -- Feminisms -- Gay identity/queer art -- Environmental art -- Anti-globalization -- Epilogue
Keywords: Art and society -- History